New acanthodrilid earthworms of genera protozapotecia and trigaster from Cuba (annelida, crassiclitellata) - Fragoso, Carlos; Rodríguez, Carlos (Instituto de Ecología, A.C., 2017)
Four new Cuban species of the family Acanthodrilidae are described from west (Protozapotecia angelesae sp.nov.), center (Protozapotecia centralis sp.nov., Protozapotecia cubensis sp.nov.) and east (Trigaster setarmata sp.nov.) regions. The new species are closely related to northeast and east Mexico (Protozapotecia and Zapatadrilus) and Puerto Rico and Virgin Islands earthworms (Trigaster). Whereas new Protozapotecia species possess two gizzards and holonephridia, Trigaster setarmata sp.nov. has three gizzards and meronephridia. Protozapotecia angelesae sp.nov. is separated from all Mexican species of the genus by the absence of typhlosole and penial setae and by presence of free lamellae in the esophagus of 11 and 12. The presence of penial setae and typhlosole relates the other two new Protozapotecia species to Mexican worms; from all of them, Protozapotecia cubensis sp.nov is separated by a dorsal pore in 4/5, free calciferous lamellae in 13 and a lateral spermathecal diverticulum, whereas Protozapotecia cubensis sp.nov. is differentiated by last hearts in 13 and calciferous lamellae in segments 13, 14 and 15. Trigaster setarmata sp.nov. is separated from the four recognized species of the genus by the presence of penial setae and racemose prostatic glands. Clarification of the origin of Cuban acanthodrilids (dispersion or vicariant events) will depend on future sampling and on the elaboration of robust molecular phylogenies.